Penerapan Disk Mill Pada UMKM Anugerah Produksi Vitamin Unggas di Desa Sekarmojo Kecamatan Purwosari - Djoko Hari Praswanto; Soeparno Djiwo; Mochtar Asroni; Lalu Mustiadi; Thomas Priyasmanu (Badan Penerbitan Universitas Widyagama Malang, 2021)
Poultry vitamins are one of the nutrients needed by breeders. This poultry vitamin serves to accelerate the growth of poultry, maintain the quality of poultry meat, improve the quality of poultry eggs, prolong poultry egg production and accelerate poultry egg production. One of the partners who was worked together with the ITN Malang team is engaged in the field of poultry vitamins production and wants to increase the turnover of poultry vitamin production. All the time, the price of poultry vitamins from factories is considered high enough so that farmers have objections to buying poultry vitamins from the factory. The community service team observed at the quality of poultry vitamins which are produced in the Purwosari area and will transfer technology to apply a disk mill in the production process which will be able to increase the production of poultry vitamins in good prices but with high quality also. In addition, the community service team will improve the packaging by used aluminum foil to avoid moisture and later will be given a logo to facilitate the sales process to breeders. After improved the packaging, it has expected can be freely marketing with the general standardization of poultry vitamins. So that farmers can get cheap and good quality poultry vitamins. From the results of the activities carried out, it was found that a disk mill machine with a capacity of 150 kg / hour. It if the production of 500 kg takes 3 hours with one workers person. So that the partners can save time and production costs. So that the profits obtained now increase 25% from previous profits. Meanwhile the packaging used by the team partners now used aluminum foil so that the product looks more attractive and is able to hold the product dry.